Kajian Kimia Dari Fraksi Etil Asetat Kulit Batang Kayu Pahit (Picrasma Javanica Bl.) - Sri Hainil; Dayar Arbain; Deddi Prima Putra (Jurnal Sains Farmasi & Klinis, 2015)
N-1 main compound from ethyl acetate fraction of kayu pahit bark (Picrasma Javanica B1) has been isolated and characterized with colom chromatography and continued with preparative chromatography. According to analized from spectrum data used ultraviolet (UV) spectroscopy, infra red (IR), 1H RMI (Resonansi Magnet Inti), 13 C RMI, Massa , COSY (Correlated Spectroscopy), HSQC (Heteronuclear Single Quantum Correlation), HMBC ( Heteronuclear Multiple Bond Correlation) and literature study showed that the compound of isolation was javanicin A.